VD_FINDINFO Décision / 2012 / 1006 vom 16. August 2012 - VD Tribunal cantonal (2012)
CLASSEMENT DE LA PROCÉDURE, ABUS DE CONFIANCE, APPROPRIATION ILLÉGITIME | 138 ch. 1 CP, 138 CP, 141 CP, 146 CP, 319 CPP (CH)